PSDB: força e limites da resposta liberal aos desafios do Brasil contemporâneo - Marcelo Soares Dulci (2010)
This thesis analyzes the role of PSDB in the contemporary Brazilian political context. Its main objective is to identify in the history of Brazilian social thought - the elements which might enlarge the understanding of the political culture that lies in the origin of PSDB and was decisive for the practical action of that party between 1988 and 2002. The main proposition of the research is that the party represents, in a specific way, a peripheric liberal worldview, based mainly on Fernando Henrique Cardoso´s thought but adding other theoretical contributions and political forces, that, at some point of history, have occupied a sort of political-ideological gap in the Brazilian party system which was formed during the process of transition to democracy.